Effects of Human Alpha-Synuclein A53T-A30P Mutations on SVZ and Local Olfactory Bulb Cell Proliferation in a Transgenic Rat Model of Parkinson Disease - Naveilhan, Philippe; Lescaudron, Laurent; Damier, Philippe; Anegon, Ignacio; Tesson, Laurent; Usal, Claire; Rémy, Séverine; Thinard, Reynald; Boyer, Cécile; Lelan, Faustine; Neveu, Isabelle (Parkinson's disease, 2011)
A transgenic Sprague Dawley rat bearing the A30P and A53T α-synuclein (α-syn) human mutations under the control of the tyrosine hydroxylase promoter was generated in order to get a better understanding of the role of the human α-syn mutations on the neuropathological events involved in the progression of the Parkinson’s disease (PD). This rat displayed olfactory deficits in the absence of motor impairments as observed in most early PD cases. In order to investigate the role of the mutated α-syn on cell proliferation, we focused on the subventricular zone (SVZ) and the olfactory bulbs (OB) as a change of the proliferation could affect OB function. The effect on OB dopaminergic innervation was investigated. The human α-syn co-localized in TH-positive OB neurons. No human α-syn was visualized in the SVZ. A significant increase in resident cell proliferation in the glomerular but not in the granular layers of the OB and in the SVZ was observed. TH innervation was significantly increased within the glomerular layer without an increase in the size of the glomeruli. Our rat could be a good model to investigate the role of human mutated α-syn on the development of olfactory deficits.